PENGARUH STRES PELAPARAN DAN SUHU TINGGI TERHADAP INDUKSI EMBRIOGENESIS MIKROSPORA TEMBAKAU - Wahidah , Baiq Farhatul (Jurnal Biologi Udayana; Vol 14 No 1 (2010): Jurnal Biologi, 2010)
The effect of treatment combination of starvation and heat shock (34oC) towards embryogenesis induction of microspores on three cultivars of Nicotiana tabacum L. cv. Petit havana SR-1, N. tabacum L. cv. Vorstenlanden, and N.tabacum L. cv. Virginia had been examined. The microspores were isolated aseptically from anthers by maceration and centrifugation. The culture was conducted in a starvation medium (B- Medium) without sugar and nitrogen source for 4, 6, 8 days at 34oC. Then, they were subcultured on embryogenesis medium (A2 medium) and were incubated at 25oC in dark. The development of cultivated microspores was relatively homogenous in which they contained of late uninucleate stage. The viability and microspores development were observed. The stain of nucleus was done using DAPI (4,6-diamindino-2-phenylindole) then the colored microspores were observed under the fluorescent microscope. During the starvation stress and heat shock (34oC), the structure of microspores changed into 3 types of embryogenic microspore. Type 1 was indentical with late uninucleate stage; in type 2 the vacuole of microspore was fragmented in periphery position with the nucleus; and type 3 the nucleus found in a cytoplasmic pocket was shifted into centre position..The simetrical division was the first division occurred in embryogenesis stage of microspores. It was occurred on the three cultivars after the incubation period. Then it will form a multicellular structure in the fourth week of N. tabacum L. cv. Vorstenlanden and N. tabacum L. cv. Virginia. Meanwhile, for N.tabacum L. cv Petit havana SR-1 the multicellular structure was formed in the second week. In the next phase, the multicellular structure developed into callus for N. tabacum L. cv. Vorstenlanden and N. tabacum L. cv. Virginia. While, for N. tabacum L. cv. Petit havana SR-1 the multicellular structure developed into globular structure.
Keywords: microspore, embryogenesis, starvation, heat shock, Nicotiana tabacum L. cv, Petit havana SR-1, N. tabacum cv.Vorstenlanden, N. tabacum cv. Virginia